2021
DOI: 10.3201/eid2709.210068
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing High Incidence and Case-Fatality Rates for Invasive Listeriosis, Germany, 2010–2019

Abstract: L isteria monocytogenes infections are primarily foodborne and cause gastrointestinal disease or invasive syndromes among infected persons (1). Because L. monocytogenes is an intracellular pathogen and because invasive listeriosis is the primary manifestation in diagnosed listeriosis, persons with defi cient cell-mediated immunity are at increased risk for its symptoms, including sepsis and meningitis. In addition, infection during pregnancy can lead to chorioamnionitis and fetal infection that can result in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 9 publications
2
29
2
Order By: Relevance
“…As ageing of the population will continue in most MS (EUROSTAT, 2021) in the coming years, it is important to raise awareness of listeriosis and its risks, especially among older people and pregnant women, associated with certain consumption habits and types of food (e.g. RTE fish products and frozen vegetables) ECDC, 2018b, 2019;EFSA BIOHAZ Panel, 2018, 2020cHerrador et al, 2019;Spa ckov a et al, 2021;Wilking et al, 2021). L. monocytogenes was identified as the causative agent in nine strong-evidence and seven weakevidence foodborne outbreaks in 2020 that together affected 120 people in the EU.…”
Section: Discussionmentioning
confidence: 99%
“…As ageing of the population will continue in most MS (EUROSTAT, 2021) in the coming years, it is important to raise awareness of listeriosis and its risks, especially among older people and pregnant women, associated with certain consumption habits and types of food (e.g. RTE fish products and frozen vegetables) ECDC, 2018b, 2019;EFSA BIOHAZ Panel, 2018, 2020cHerrador et al, 2019;Spa ckov a et al, 2021;Wilking et al, 2021). L. monocytogenes was identified as the causative agent in nine strong-evidence and seven weakevidence foodborne outbreaks in 2020 that together affected 120 people in the EU.…”
Section: Discussionmentioning
confidence: 99%
“…12 Contamination is often through ready-to-eat foods where the pathogen can be present in high amounts due to its ability to grow under refrigeration temperatures. 13 The pathology varies from a noninvasive form (gastroenteritis, febrile diarrhea, headache) to invasive listeriosis, which manifests in more serious symptoms such as septicemia and meningitis. The effectiveness of pediocin PA-1, as an anti- Listeria preservative in food, has been studied for decades with many studies using ALTA 2341 (Quest International, Irvine, CA, USA), a commercially available pediocin-containing P. acidilactici syrup fermentate.…”
Section: Introductionmentioning
confidence: 99%
“…Listeriosis is a rare but severe disease caused by Listeria monocytogenes ( L. monocytogenes ), a ubiquitous food-borne bacterial pathogen [ 1 , 2 ]. People principally get listeriosis by the ingestion of contaminated food [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, it has a predilection to infect pregnant women, which is at approximately 10–100 times greater risk for infection than the general population [ 5 7 ]. In Europe and North America, it has been observed previously that the proportion of pregnancy-associated listeriosis out of the total listeria infections ranges from 9 to 20% [ 2 , 8 10 ]. Moreover, recent studies performed in China showed that more than half of listeria cases were pregnancy-associated infections [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%